1996
DOI: 10.1021/cm9600135
|View full text |Cite
|
Sign up to set email alerts
|

Lithographic Properties of Poly(tert-butyl methacrylate)-Based Block and Random Copolymer Resists Designed for 193 nm Wavelength Exposure Tools

Abstract: Block and random copolymers were prepared using the monomers tert-butyl methacrylate and [3-(methacryloxy)propyl]pentamethyldisiloxane. The polymers have low absorption at 193 nm wavelength, making them attractive candidates for 193 nm wavelength imaging. The resists have a high resistance to oxygen reactive ion etching, making them suitable for the imagable layer of a bilevel resist system. After exposure, the block copolymers have better development behavior in aqueous base than that of the corresponding ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Cyclohexane is a solvent for PDMS and a nonsolvent for PS. 5,6 Therefore, the fact that the copolymer was soluble in cyclohexane shows that PDMS successfully was attached to the PS. In contrast, bromobenzene is a good solvent for PS and a non-solvent for PDMS.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cyclohexane is a solvent for PDMS and a nonsolvent for PS. 5,6 Therefore, the fact that the copolymer was soluble in cyclohexane shows that PDMS successfully was attached to the PS. In contrast, bromobenzene is a good solvent for PS and a non-solvent for PDMS.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…These data are consistent with PDMS, which is not soluble in bromobenzene. 5,6 The bromobenzene solution was precipitated into methanol. The product was dried in a vacuum oven at 50°C to give a 66.6% yield (0.8 g) of PDMS-PS-PDMS triblock copolymer (M w /M n ϭ 101/52 kDa).…”
Section: Synthesis Of Triblock Pdms-ps-pdms (Iv) By the Acid-catalyzementioning
confidence: 99%
See 2 more Smart Citations
“…For 193 nm lithography, Gabor et al 4,5 focused on block and random copolymers using tert-butyl methacrylate (t-BMA) and a siloxane tertbutyl methacrylate [3-(methacryloxy)propyl] pentamethyldisiloxane ( Figure 1a). They showed that block copolymers develop better in aqueous base than the corresponding random copolymers because of the higher percentage of the tert-butyl units that are cleaved in block copolymers and also because they can potentially develop in a micellar manner, where only one block needs to be soluble in the aqueous base.…”
Section: Polymer Resists For 193 Nm Lithographymentioning
confidence: 99%